PERLINDUNGAN HUKUM TERHADAP HAK-HAK REPRODUKSI PEKERJA WANITA (PERSPEKTIF UNDANG-UNDANG KETENAGAKERJAAN DI INDONESIA DAN MALAYSIA) - Miladiyanto, Sulthon; Ariyanti, Ariyanti (Jurnal Panorama Hukum, 2017)
Occupational health and safety is one of the requirements set in international relations that must be met by all members including Indonesia and Malaysia. In an effort to provide protection to workers, Indonesia and Malaysia have ratified the International Labor Organization (but not all ILO conventions are ratified). Ratifying the convention, bringing the consequences that both countries must meet the ILO standards in implementing legal protection of their workers. The ILO aims to promote social justice, the protection of women workers and the promotion of equality between men and women, to obtain decent and productive employment in conditions of freedom, equity, security and dignity and participation in unions. Although the principle of equality, opportunity and treatment between men and women has been widely accepted in many countries, in practice injustice exists within the union environment both locally and locally.